Energy Neutral Clustering for energy harvesting wireless sensors networks - Shuai Peng; Chor Ping Low (Proceedings - IEEE International Conference on Networks, 2013)
For wireless sensors with energy harvesting capability, energy neutral operation can be achieved by ensuring that the amount of energy consumed is no more that the amount of energy harvested in certain period of time. As a result, an energy neutral sensor will be able to sense and relay useful information to the destination perpetually. In this paper, we propose a hierarchical routing protocol that can cluster sensors in the network in a way that all sensors will be able to maintain energy neutral status. Based on a novel Cluster Head Group mechanism, our proposed routing protocol can provide consistent data delivery with a low control message overhead. This in turn helps to improve the total amount of information bits that can be relayed to destinations as compared with other traditional clustering protocols. Simulations confirm that our proposed routing protocol can provide such improvement while ensuring the energy neutral status of the whole network.